Biofuel cropping system impacts on soil C, microbial communities and N₂O emissions - McGowan, Andrew R. (Kansas State University, 2015)
Substitution of cellulosic biofuel in place of gasoline or diesel could reduce greenhouse gas (GHG) emissions from transportation. However, emissions of nitrous oxide (N₂O) and changes in soil organic carbon (SOC) could have a large impact on the GHG balance of cellulosic biofuel, thus there is a need to quantify these responses in cellulosic biofuel crops. The objectives of this study were to: (i) measure changes in yield, SOC and microbial communities in potential cellulosic biofuel cropping systems (ii) measure and characterize the temporal variation in N₂O emissions from these systems (iii) characterize the yield and N₂O response of switchgrass to N fertilizer and to estimate the costs of production. Sweet sorghum, photoperiod-sensitive sorghum, and miscanthus yielded the highest aboveground biomass (20-32 Mg ha⁻¹). The perennial grasses sequestered SOC over 4 yrs, while SOC stocks did not change in the annual crops. Root stocks were 4-8 times higher in the perennial crops, suggesting greater belowground C inputs. Arbuscular mycorrhizal fungi (AMF) abundance and aggregate mean weight diameter were higher in the perennials. No consistent significant differences were found in N₂O emissions between crops, though miscanthus tended to have the lowest emissions. Most N₂O was emitted during large events of short duration (1-3 days) that occurred after high rainfall events with high soil NO₃₋. There was a weak relationship between IPCC Tier 1 N₂O estimates and measured emissions, and the IPCC method tended to underestimate emissions. The response of N₂O to N rate was nonlinear in 2 of 3 years. Fertilizer induced emission factor (EF) increased from 0.7% at 50 kg N ha⁻¹ to 2.6% at 150 kg N ha⁻¹. Switchgrass yields increased with N inputs up to 100-150 kg N ha⁻¹, but the critical N level for maximum yields decreased each year, suggesting N was being applied in excess at higher N rates. Yield-scaled costs of production were minimized at 100 kg N ha-1 ($70.91 Mg⁻¹). Together, these results show that crop selection and fertilizer management can have large impacts on the productivity and soil GHG emissions biofuel cropping systems.
Keywords: Biofuel; Soil carbon; Nitrous oxide; Greenhouse gases; Agronomy (0285); Alternative Energy (0363); Soil Sciences (0481)